낙동강 하구수역 수질오염에 관한 연구 - 임부상 (연세대학교 보건대학원, 1988)
[한글] 자연계에서 물은 가장 풍부한 자원이지만 질과 양에서 시간적, 공간적 분포의 제한을 받고 있다. 대부분의 물은 수문학적 순환형태로 내리는 담수에 한정되고 있으며, 수자원 개발의 궁극적 목표는 계절적 또는 지역적으로 편재된 수자원을 가장 경제적이고 효율적으로 조절하는 것이라 할 수 있다 우리나라는 대륙임해성 기후조건을 갖추고 있어 비교적 풍부한 수자원을 보유하고 있으면서도 지형상 하천의 유로가 짧고 경사가 급하여 일시적 유출로 인한 홍수피해와 막대한 수자원 손실을 당하고 있으며 이러한 홍수피해 방지와 수자원 확보를 위한 대책과 수단의 일환으로서 댐의 건설, 홍수 조절지의 건설, 방조제 및 하천제방 건설과 하천개수사업등이 활발히 진행되고 있다. 낙동강은 남한 전체 면적의 1/4에 해당하는 넓은 유역 면적을 가진 남한 제2의 강으로서 유역에는 중요도시 및 공업단지와 넓은 농경지가 인접되어 있는 중요한 하천이다. 더우기 하구에는 물의 손실을 방지하고 염분의 침수를 차단하여 보다 양질의 용수를 공급하기 위하여 1983년부터 을숙도를 가로지르는 하구둑을 건설하여 1987년에 준공하였다. 하구둑의 기능이 해수의 침수를 막아 용수로서의 효용이 높은 수자원을 획득하는 데 있으므로 이의 건설은 불가피하게 담수와 해수의 혼합에 의하여 야기되는 하구 수질의 특성에 변화를 일으키게 된다. 본 연구는 낙동강 하구수역을 대상으로 1985년 3월부터 1988년 2월까지 3년간에 걸쳐 하구수역에서 의도별 및 계절별 수질오염도를 조사 분석하여 다음과 같은 결론을 얻었다. 1. 수온은 상류지역에서 기온과 밀접한 관계가 있었으며 pH는 대체로 5.0∼8.0의 분포를 나타내었다. 염분도는 조사지점 st.2인 구포까지 해수의 영향이 나타내었다. 2. BOD는 3개년 평균치가 3.3± 1.1㎎/ℓ, COD는 3개년 평균치가 4.6±1.8㎎/ℓ로서 계절별 큰 구분 없이 높았으며 부산직할시상수취수원이 있는 조사지점 st.1인 물금지역에서 BOD의 3개년 평균치가 3.1±0.8㎎/ℓ로서 1978년에 조사한 2.6±0.2㎎/ℓ보다 높아진 것으로 조사되어 상류지역에서의 BOD오염도가 증가되어 있는 것으로 조사 분석되었고 질소 등의 영양염류는 계속적으로 많은 양이 하구호소로 유입되고 있었으며 인산염 인(PO^^4 -P )의 경우 봄, 가을의 농도 44±33㎍/ℓ, 65±25㎍/ℓ로서 여름, 겨울의 농도 26±10㎍/ℓ, 38±19㎍/ℓ보다 높았다. 3. Chlorophyll-a의 분포는 3개년 평균치가 10.9±9.2㎎/㎥이었으며 계절별로는 봄철에 15.7±9.8㎎/㎥으로 가장 낮은 겨울철7.0±2.4㎎/㎥보다 2배 이상 값을 나타낸 것으로 조사분석 되었다. 4. 중금속은 대체적으로 하구수역에서는 환경기준치 이하로 조사분석 되었다. 이상의 결과로 보아 현재 환경기준 3급 수질을 나타내고 있는 낙동강 하구수역의 수질변화는 상류 및 부산서부지역 공단 및 주거지역으로부터 유입되는 오염부하량과 유수량에 따라 복합적으로 나타날 것으로 사료된다. 따라서 하구호소에 영향을 미칠 수 있는 오염부하량의 최소화와 갈수기에 희석수를 확보하는 대책이 요망된다. [영문] In the natural world, water is the most rich resources, but in quality and quantity, it is restricted by time and space. The most of the water use is limitted to fresh water. The ultimate purpose of developing the wafer resources aims for the most economical and effective management of it. Although our country has rich water resources, tapographically, the flow passage in the river is so short and steep and thus the water resources is suffered by the flood-damages due to the out-flow of the water during the rain season and a vast damages during the natural flow. For the prevention of these flood damages, a counter-measure to secure the water resources, and as a means of water resources conservation, many dams, assisting tanks, and canal dikes are under construction and various stream improvement works are being performed. The Nakdong river is the 2nd longest river in South-Korea and it occupies as wide waters basin area as one quarter of the whole South-Korean waters water basin areas it is important river for it Lies adjacent to main cities, industrial sites and vast farm-Lands. Futhermore, at the rivers estuary in 1983,estuary barrage acrossing the Eulsuk island was began to construct and completed in 1987, the purpose of this construction was to prevent the Loss of water, terminates the salty water infiltration from the sea and supplying the more clean using water. The function of the estuary barrage was to keep the salty water infiltration from the sea and to aquire the high effective water resources and thus it appears to be enevitable to construct it. consequently, it changes the character of estuarine water quality which may be caused by mixing with the flesh water and salty water. This study was carried out for three years; from Match 1985 to February 1988 at Nakdong river estuary. Water samples from 10 survey stations were analyzed for various water quality items such as BOD, COD, Phosphate and heavy metals. And concluded as the followings; 1. Water temperature has close correlationship with air temperature in upper stream area. And pH was in range of 5.5-8.0,salty water has infiltrated to Gupo, St.2. 2. Average concentration of BOD for the three years in the study area was 3.3± 1.1㎎/ℓ, it of COD was 4.6±1.8㎎/ℓ. Generally, BOD. COD was high without big difference in the season. In station 1 located by water supply facility of Busan city, concentration of BOD for the three years was 3.1±0.8㎎/ℓ, which was higher than the value which was investigated in 1978. The abundant nutrients such as was flowing ceaselessly in to the river estuary, the concentration of phosphate(po^^4 -p) was higher in spring and fall than summer and winter. 3. Average concentration of chlorophyll-a for the bast three years was 10.9±9.2㎎/㎥, it was tn times higher in spring than winter. 4. The concentration of heavy metals was generally bellow the environmental standards. In considering the above results we consider the change of water quality in the river-estuary waters of Nakdong river, which indicates 3rd grade water quality of environemntal standard, occurs compoundly due to the pollutant quantity and flowing from the upper stream flows. Therefore it is demanded that we take counter-measures to dear-easing the quantity of pollutants at the uppers stream area which may inference to the Nakdong river estuary lake and secure the water for dilution in dry season.
환경관리학과/석사